2020
DOI: 10.1111/ele.13585
|View full text |Cite
|
Sign up to set email alerts
|

Invasion growth rate and its relevance to persistence: a response to Technical Comment by Ellner et al.

Abstract: Ellner et al. (2020) state that identifying the mechanisms producing positive invasion growth rates (IGR) is useful in characterising species persistence. We agree about the importance of the sign of IGR as a binary indicator of persistence, but question whether its magnitude provides much information once the sign is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Importantly, the magnitude of these auto-correlations can lead to different ecological outcomes due to differences in transient versus long-term responses of species to changing interaction rates [Bender et al, 1984, Hastings et al, 2018]. Understanding how these effects combine across multiple species, how they interact with other coexistence mechanisms [Chesson, 2018], and how they are impacted by demographic stochasticity [Pande et al, 2020a, Ellner et al, 2020, Pande et al, 2020b] provide significant challenges for future work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the magnitude of these auto-correlations can lead to different ecological outcomes due to differences in transient versus long-term responses of species to changing interaction rates [Bender et al, 1984, Hastings et al, 2018]. Understanding how these effects combine across multiple species, how they interact with other coexistence mechanisms [Chesson, 2018], and how they are impacted by demographic stochasticity [Pande et al, 2020a, Ellner et al, 2020, Pande et al, 2020b] provide significant challenges for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding how these effects combine across multiple species, how they interact with other coexistence mechanisms [Chesson, 2018], and how they are impacted by demographic stochasticity [Pande et al, 2020a, Ellner et al, 2020, Pande et al, 2020b] provide significant challenges for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Some progress has been made on understanding the role of temporal variation on coexistence times [Pande et al, 2020b, Ellner et al, 2020, Pande et al, 2020a]. For example, using the methods presented here, [Ellner et al, 2020] found that the mean invasion growth rates for the lottery model [Warner and Chesson, 1985] are strongly correlated with intrinsic coexistence times.…”
Section: Discussionmentioning
confidence: 99%
“…Stochasticity can be a determinant factor of invasion success in the early stages of establishment so that the invasion growth rate is not necessarily a good quantitative metric of success (Pande et al., 2020b). Here, we consider whether invasion is deterministically possible (Pande et al., 2020a), and more importantly, what will be its impact if successful, assuming that in that case, the invader population will be large enough that demographic stochasticity can be neglected (Blackburn et al., 2015).…”
Section: An Extension Of Invasion Analysismentioning
confidence: 99%